2020
DOI: 10.3389/fneur.2020.00796
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Contralateral Hearing Loss in Patients With Sporadic Vestibular Schwannoma

Abstract: Background and Introduction: Vestibular schwannomas (VSs) are the most common tumors of the cerebellopontine angle, typically presenting unilaterally with ipsilateral sensorineural hearing loss (SNHL). The mechanism of tumor-induced hearing loss has recently been shown to be related to secreted tumor factors, in addition to mechanical compression of the adjacent auditory nerve, and these factors may percolate through CSF or blood to affect contralateral hearing as well. Methods: This is a retrospective study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 43 publications
4
20
0
Order By: Relevance
“…stm.sciencemag.org/cgi/content/full/13/602/eabd4816/DC1 Materials and Methods Figs. S1 to S9 Tables S1 to S11 Data file S1 References (81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97) View/request a protocol for this paper from Bio-protocol.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…stm.sciencemag.org/cgi/content/full/13/602/eabd4816/DC1 Materials and Methods Figs. S1 to S9 Tables S1 to S11 Data file S1 References (81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97) View/request a protocol for this paper from Bio-protocol.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Recent studies have demonstrated the role of secreted factors in causing hearing loss in pathologies such as vestibular schwannoma, which can present with sudden SNHL and for which the audiometric hallmark is disproportionate loss in word recognition relative to threshold shift; undiagnosed Meniere's and autoimmune ear disease may also increase risk to bilateral hearing ( 27 , 30 , 31 ). While none of the patients in the current study were known to have other otologic disease at the time of initial evaluation for ISSHNL, sudden hearing loss can often serve as the initial presentation for an underlying inflammatory or autoimmune mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses of hearing loss progression by isolated threshold and word recognition criteria could then be performed as secondary endpoints. As an isolated metric, a three-tone PTA was chosen for threshold analysis because this metric is most closely associated with speech reception thresholds and thus of highest clinical utility ( 25 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…In most patients, the impairment is typically sensorineural in the ear ipsilateral to the tumor, and hearing deteriorates gradually ( 4 ). However, in some cases, hearing loss presents in the unaffected ear and worsens suddenly ( 5 , 6 ). In a recent retrospective study involving 661 SVS patients, the researchers noticed that there might exist a long-term risk of hearing loss in the contralateral ear ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases, hearing loss presents in the unaffected ear and worsens suddenly ( 5 , 6 ). In a recent retrospective study involving 661 SVS patients, the researchers noticed that there might exist a long-term risk of hearing loss in the contralateral ear ( 5 ). After surgical and radiation therapy, hearing dysfunction is more prevalent.…”
Section: Introductionmentioning
confidence: 99%